A Restructuring (IN)Tangible cultural Heritage of Rural Zimbabweans: Sustaining and Fulfilling Livelihoods - Rutsate, Jerry; Rutsate, Sipho Heleni (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2021)
The documentation and promotion of African experiences grew out of the need to mitigate the weaknesses of the oral tradition through which the history of the presumed complex indigenous African creative undertaking was defined. The paucity of written records was further accentuated by the 2003 UNESCO Convention for Safeguarding Intangible Cultural Heritage. The methodical essential tools of accurate collection and critical analysis were deemed to be the better organized forms of freezing experiences. Skewed towards the sciences, research on both pre and post-independent Zimbabwean indigenous intellectual property has not yielded much benefit to the researched practitioners. To this end, Higher Education has failed to fulfil society’s expectations for pace-setting development and sustainability. In the stir of the world-wide decline of industries owing to trade liberalization and the development of free market as well as the adoption of the European Union ‘high-road competitiveness’ policy (Aiginger 2014), this chapter intends to reground creative and cultural industries by embracing a potential symbiotic relationship between informal transmission of authentic (in)tangible cultural heritage and the formal living archiving and commodification of the indigenous knowledge systems of ethnic groups of people in Zimbabwe. The case study for this paper, which commenced in 2015, is the Dzimbadzamabge Cultural Heritage Enterprise Institute located in Nemamwa Rural District.